Leadership - Lussier, Robert N. (Thomson/SouthWestern, 2007)
Learn tomorrow's leadership strategies today. LEADERSHIP combines traditional theories with cutting-edge developments to bring you the leadership textbook you have to own if you want to succeed in tomorrow's workforce. Plus, this edition comes with hands-on skill building exercises so you can learn by doing. And with countless study aids built right into the textbook, you'll have all you need to ace the test as well